A System to Enable Mixing Controlled Combustion With High Octane Fuels Using a Prechamber and High-Pressure Direct Injector - Dempsey, Adam B.; Zeman, Jared; Wall, Martin (Frontiers in Mechanical Engineering, 2021)
The demand for transportation energy is growing and thus improving the efficiency and reducing the pollutant emissions from this energy sector is critical. Transportation has historically been powered by the internal combustion engine (ICE). Many alternative technologies are being evaluated to replace the ICE, such as hydrogen fuel cells and battery electrics. These technologies appear attractive at the vehicle-level but have many challenges regarding life cycle emissions and lack of infrastructure. A more pragmatic approach would be to use the current liquid fuels infrastructure with cleaner burning, renewable fuels that have the potential to be carbon neutral, such as low carbon alcohols like methanol, ethanol, propanol, and butanol. These alternative fuels tend to have a high-octane number, making them great candidates for conventional spark ignition (SI) engines. However, SI engines are plagued by several challenges when it comes to high load operation, such as pre-ignition, knock-limited peak torque, poor snap torque response, high levels of cyclic variability, and sensitivity to varying fuel properties. The objective of this research is to develop a technology that will allow high octane fuels to be utilized in engines and utilize robust mixing controlled combustion. The proposed technology is a system which utilizes an active prechamber in the shape of an annulus and a high-pressure direct fuel injector. The active prechamber and the high-pressure direct injector use the same liquid fuel, which could be any fuel that has relatively high volatility and high resistance to autoignition (i.e., high-octane number). The active prechamber is fired late in the compression stroke and hot jet flames are ejected from the prechamber. These jets ignite the direct injected fuel sprays near top dead center, establishing a mixing controlled combustion event. This will allow for robust operation across the full engine operating space with clean burning renewable fuels, without the shortcomings of SI engines regarding knock-limited operation and part load efficiency.